Edukasi Cinta Bangga Paham (CBP) Rupiah Terhadap Siswa SMP Negeri 1 Pendopo Barat Kabupaten Empat Lawang - Albie, Farhat; Yosy Arisandi; Fryanti, Yunida Een (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This Community Service Activity, conducted through a Service Learning and Face-to-Face approach, aimed to enhance students’ financial literacy, particularly regarding the importance of loving, being proud of, and understanding the Rupiah as a symbol of national sovereignty. Held from January 10 to May 5, 2025, the program targeted 68 student council (OSIS) members as agents of change by implementing CBP values in a participatory and practical manner. The main issue addressed was the limited access to financial education due to the geographical and administrative challenges faced by Empat Lawang Regency, located at the far edge of South Sumatra Province and geographically closer to Bengkulu, resulting in insufficient outreach from Bank Indonesia. To overcome this, the implementer conducted intensive coordination with the school principal and teachers, and directly engaged students through simulations and interactive discussions. The results showed a significant increase in students' understanding based on pre- and post-tests. A total budget of Rp329,000 was efficiently utilized to support the program, including educational materials, banners, and door prizes. Recommendations for future service activities include expanding the target audience to all students, diversifying educational media, and establishing broader collaborations with financial institutions to enhance the long-term impact of financial literacy. Keywords: CBP Rupiah, Financial Literacy, Community Service.